New Technology in Marine Logistics Warehouse Management - Juswan Sade (Collaborate Engineering Daily Book Series, 2024)
The marine logistics industry faces challenges in improving efficiency, reducing operational costs, and supporting environmental sustainability. One crucial aspect that can be optimized is warehouse management, which is responsible for the storage, handling, and distribution of cargo. This research aims to explore the application of new technologies such as the Internet of Things (IoT), artificial intelligence (AI), robotics, automation, and green technologies in marine logisticswarehousemanagement. Themethodology used includes a comprehensive literature review, in-depth interviews with industry experts, and analysis of case studies of new technology implementation in marine logistics companies. The results revealed significant opportunities and benefits from the implementation of new technologies, such as improved visibility and real-time monitoring of cargo, optimization of cargo storage and handling, increased productivity and safety, and reduced operational carbon footprint. However, challenges such as initial investment costs, data security, system interoperability, and human resource training needs must be overcome. This research presents a comprehensive implementation strategy, including cost-benefit analysis, development of industry standards, implementation of strict security protocols, and collaboration between industry, government, and standardization bodies.A conceptual framework is developed to provide practical guidance for the marine logistics industry to effectively implement new technologies and optimize their benefits. By adopting new technologies appropriately, the marine logistics industry can improve its competitiveness and global supply chain performance, and support environmental sustainability.